Advanced human nutrition - Medeiros, Denis M., 4 0 16; 1964-;1964- Wildman, Robert E. C.,;Wildman, Robert E. C.; 5 (Sudbury, MA : Jones & Bartlett Learning, 2012)
Provides an in-depth overview of the human body and details the importance of nutrients from a biochemical, physiological, and molecular perspective--Back cover.
Foundations of the human body -- Digestion and absorption -- Carbohydrates : energy, fiber and more -- Lipids : fatty acids, triglycerides, phospholipids, and sterols -- Proteins and amino acids : function, quantity, and quality -- Water -- Metabolism, energy balance, and body weight -- Nutrition and exercise -- Fat-soluble vitamins -- Water-soluble vitamins -- Major minerals -- Minor minerals.
Rev. ed. of: Advanced human nutrition / Robert E.C. Wildman, Denis M. Medeiros. 2000.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Nutrition.;Nutrition.; 20; 2